Analysis of Sharia Compliance and Islamic Corporate Identity Impact on Financial Performance: Evidence from Indonesian Islamic Banks (2019-2022) - Puspita, Sari Maylina; Suryanto, Tulus; Iqbal, Muhammad (Li Falah: Journal of Islamic Economics and Business, 2024)
This study examines the relationship between Sharia compliance measures, Islamic corporate identity, and financial performance in Indonesian Islamic banks. Using panel data from seven Islamic commercial banks over the 2019-2022 period, the study employs three Sharia compliance indicators: Islamic Income Ratio (IsIR), Profit Sharing Ratio (PSR), and Islamic Investment Ratio (IIR), along with Islamic Corporate Identity (ICI) as independent variables. Financial performance is measured through Return on Assets (ROA). The research utilizes panel data regression analysis with a fixed effect model validated through Chow and Hausman tests. Results indicate that PSR and ICI have significant negative effects on financial performance, while IIR demonstrates a significant positive influence. Interestingly, IsIR shows no significant impact on financial performance. The model explains 85.55% of the variation in financial performance, suggesting strong explanatory power. These findings provide valuable insights for Islamic banking regulators and practitioners in understanding the complex relationship between Sharia compliance, corporate identity, and financial performance in the Islamic banking sector.